STRATEGI PENGEMBANGAN FASILITAS OBJEK WISATA PANTAI PASIR JAMBAK PADANG - Mesta, Qoriah; Silfeni, Silfeni; Suyuthie, Hijriyantomi (Journal of Home Economics and Tourism, 2016)
This research is aims to describe the development strategy of the facilities attraction  at Pasir Jambak Beach Padang using a SWOT analysis in terms of internal factors including: the strength of tourist facilities and the weakness of tourist facilities , while the external factors include : opportunities in developing tourist facilities and the threat in developing tourist facilities. This type of research is descriptive qualitative. Techniques of collecting data are using interviews, observation, and documentation. The results of this research stated that: 1). The strength of the attraction at Pasir Jambak beach is already available in part of infrastructure and facilities like electricity, water, telecommunication networks (mobile phone signal), stage entertainment, prayer rooms, and toilets, lodging, gazebo, and a parking lot. 2). The weakness is the lack of assistance from the government in developing an attraction, a lack of public awareness in the maintenance of tourist facilities, the condition of the entrance to the tourism site is still broken , there is no health infrastructure, no security posts and public transport to tourism site, and there are no restaurants, no souvenir shops and no game facilities. 3). Opportunity that Pasir Jambak beach had to complete the facilities are  tourist area that is wide enough and there are still many vacant land, sea waves are well suited to water sports, and existing investors. 4). Threats in developing facilities attraction at Pasir Jambak  Beach is there are no support from the surrounding sociality in the existence of tourist facilities, lack of human resources that are competent in managing tourist facilities.  The strategy for the development of facilities Pasir Jambak Beach attraction that can be done are: Expanding the sale network. The government may allocate funds for the procurement and maintenance of tourist facilities. Cooperating with the local music industry to bring entertainment. Repairing the road infrastructure. Government agencies embrace local communities through tourism awareness by education briefing.   Kata Kunci: Strategi, Pengembangan, Fasilitas Wisata, Analisis SWOT